LARGE-SCALE LATERAL HEAT AND FLUID TRANSPORT IN THE SEAFLOOR: REVISITING THE WELL-MIXED AQUIFER MODEL - Rosenberg N.D.; Fisher A.T.; Stein J.S. (My University, 2000)
Large-scale, lateral fluid flow through oceanic crust provides an explanation for regionally low heat flow in several seafloor settings. A well-mixed aquifer (WMA) model provides a quantitative and conceptual tool for explaining anomalously low heat flow based on an analytical representation of fluid and heat flow, assuming lateral fluid flow in basement in a layer directly below the ocean sediments. We present an extended well-mixed aquifer (EWMA) model that allows fluid flow at greater depths within the oceanic crust. Flow through a deeper permeable layer extracts more heat than equivalent flow through a shallower layer of equal thickness, and may help to reconcile global heat flow and seafloor permeability data, since deeper flow does not require velocities as great as shallow flow to account for the same heat loss, and thus permeability can be lower. Numerical simulations that test the hydrodynamic validity of the WMA and EWMA equations indicate that the analytical models provide reasonable approximations of large-scale, lateral heat transport when lateral fluid flow in the crust is confined to thin layers. The efficiency of lateral heat transport is reduced as vertical mixing within the lateral flow layer increases.
Keywords: OCEAN FLOORS; HYDROTHERMAL CONDITIONS; HEAT FLOW; FLUID DYNAMICS